Severe childhood Guillain‐Barré syndrome associated with Mycoplasma pneumoniae infection: a case series. Issue 2 (June 2015) - Meyer Sauteur, Patrick M.; Roodbol, Joyce; Hackenberg, Annette; de Wit, Marie‐Claire Y.; Vink, Cornelis; Berger, Christoph; Jacobs, Enno; van Rossum, Annemarie M. C.; Jacobs, Bart C.
Abstract We report seven children with recent Mycoplasma pneumoniae infection and severe Guillain‐Barré syndrome (GBS) that presented to two European medical centres from 1992 to 2012. Severe GBS was defined as the occurrence of respiratory failure, central nervous system (CNS) involvement, or death. Five children had GBS, one Bickerstaff brain stem encephalitis (BBE), and one acute‐onset chronic inflammatory demyelinating polyneuropathy (A‐CIDP). The five patients with severe GBS were derived from an original cohort of 66 children with GBS. In this cohort, 17 children (26%) had a severe form of GBS and 47% of patients with M. pneumoniae infection presented with severe GBS. Of the seven patients in this case series, five were mechanically ventilated and four had CNS involvement (two were comatose). Most patients presented with non‐specific clinical symptoms (nuchal rigidity and ataxia) and showed a rapidly progressive disease course (71%). Antibodies against M. pneumoniae were detected in all patients and were found to be intrathecally synthesised in two cases (GBS and BBE), which proves intrathecal infection. One patient died and only two patients recovered completely. These cases illustrate that M. pneumoniae infection in children can be followed by severe and complicated forms of GBS. Non‐specific clinical features of GBS in such patients may predispose a potentially life‐threatening delay in diagnosis.